Bsep/Abcb11 knockout ameliorates Schistosoma mansoni liver pathology by reducing parasite fecundity - Macháček, Tomáš; Fuchs, Claudia D; Winkelmann, Franziska; Frank, Marcus; Scharnagl, Hubert; Stojakovic, Tatjana; Sombetzki, Martina; Trauner, Michael (Liver international, 2023)
BACKGROUND AND AIMS: Schistosoma mansoni infection is one of the worldwide leading causes of liver fibrosis and portal hypertension. The objective of this study was to evaluate whether polyhydroxylated bile acids (BAs), known to protect mice from the development of acquired cholestatic liver injury, counteract S. mansoni-induced inflammation and fibrosis. METHODS: Adult FVB/N wild type (WT) and Abcb11/Bsep-/- mice were infected with either 25 or 50 S. mansoni cercariae. Eight weeks post infection, effects on liver histology, serum biochemistry, gene expression profile of proinflammatory cytokines and fibrotic markers, hepatic hydroxyproline content and FACS analysis were performed. RESULTS: Bsep-/- mice infected with S. mansoni showed significantly less hepatic inflammation and tendentially less fibrosis compared to infected WT mice. Despite elevated alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase levels in infected Bsep-/- mice, inflammatory cells such as M2 macrophages and Mac-2/galectin-3+ cells were reduced in these animals. Accordingly, mRNA-expression levels of anti-inflammatory cytokines (IL-4 and IL-13) were increased in Bsep-/- mice upon infection. Furthermore, infected Bsep-/- mice exhibited decreased hepatic egg load and parasite fecundity, consequently affecting the worm reproduction rate. This outcome could arise from elevated serum BA levels and lower blood pH in Bsep-/- mice. CONCLUSIONS: The loss of Bsep and the resulting changes in bile acid composition and blood pH are associated with the reduction of parasite fecundity, thus attenuating the development of S. mansoni-induced hepatic inflammation and fibrosis.
Keywords: Liver; infection; játra; Inflammation; fertilita; bile acids; cytokiny; jaterní cirhóza; Parasites; zánět; Liver Cirrhosis; Mice; Cytokines; žlučové kyseliny a soli; paraziti; Schistosoma mansoni; zvířata; Bile Acids and Salts; Fertility; Schistosomiasis mansoni; myši; liver fibrosis; anti-inflammatory; schistosomiasis mansoni; Animals